2020
DOI: 10.1101/2020.03.01.972265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolving widespread incomplete and uneven archaeal classifications based on a rank-normalized genome-based taxonomy

Abstract: The increasing wealth of genomic data from cultured and uncultured microorganisms provides the opportunity to develop a systematic taxonomy based on evolutionary relationships. Here we propose a standardized archaeal taxonomy, as part of the Genome Taxonomy Database (GTDB), derived from a 122 concatenated protein phylogeny that resolves polyphyletic groups and normalizes ranks based on relative evolutionary divergence. The resulting archaeal taxonomy is stable under a range of phylogenetic variables, including… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 78 publications
1
31
0
Order By: Relevance
“…Notably, the topology of our complete phylogenetic tree (Fig. 2a) within the archaeal clade is mostly consistent with the tree obtained in a preliminary analysis of a larger set of archaeal genomes and a larger marker gene set ( 26 ). Taking into account these observations and the fact that we used the largest set of Asgard archaea and other archaea compared to all previous phylogenetic analyses, the appearance of the 3D topology in our tree indicates that the origin of eukaryotes from within Asgard cannot be considered a settled issue.…”
Section: Resultssupporting
confidence: 84%
“…Notably, the topology of our complete phylogenetic tree (Fig. 2a) within the archaeal clade is mostly consistent with the tree obtained in a preliminary analysis of a larger set of archaeal genomes and a larger marker gene set ( 26 ). Taking into account these observations and the fact that we used the largest set of Asgard archaea and other archaea compared to all previous phylogenetic analyses, the appearance of the 3D topology in our tree indicates that the origin of eukaryotes from within Asgard cannot be considered a settled issue.…”
Section: Resultssupporting
confidence: 84%
“…Briefly, the NCBI taxonomy associated with every fungal genome was obtained from the NCBI Taxonomy FTP site on January 17, 2020. PhyloRank linearly interpolates the RED values of every internal node according to lineage-specific rates of evolution under the constraints of the root being defined as zero and the RED of all present taxa being defined as one 57,79 .…”
Section: Red Indexmentioning
confidence: 99%
“…Our results have shown that formatting and correcting taxonomy and other metadata are critical components of reference database generation and management prior to applications for sequence classification, e.g., to standardize taxonomic ranks across entries [87]. We have already implemented functions in RESCRIPt to format the popular SILVA rRNA gene and NCBI GenBank databases, and are planning future support for parsing and editing other taxonomy formats, as well as mapping between these formats [71].…”
Section: The Curation Problemmentioning
confidence: 99%
“…These curational efforts result in a well integrated suite of biological information that can be interrogated through a variety of means and data types [25,88]. The GTDB extracts and curates data from both NCBI-RefSeq and NCBI-GenBank to generate a phylogeny of archaea and bacteria from roughly 120 ubiquitous single-copy proteins [23,87]. This phylogeny is used to inform microbial taxonomy, especially in cases where a given taxonomy is observed to be polyphyletic.…”
Section: The Evaluation Problemmentioning
confidence: 99%
See 1 more Smart Citation